Fuel Policy: A Study in Applied Economics - Posner, Michael V. (London: Macmillan, 1973)
This book can be seen as an essay on the interrelations among four industries- coal, gas, electricity, oil in the United Kingdom. It is an assumption of this book, which it is for the reader to test that there exist sound economic reasons for regarding the four industries as a 'natural unit' for policy-making, and that therefore the attempt to build a common policy for the industries has some sound economic rationale.
Includes index: p. 349-355.
Includes bibliographical references.
ne 5/04/2018
Loans
Keywords: Fuel Trade; Power Resources